2015
DOI: 10.1007/s10973-015-4742-6
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and thermal characteristics of low-grade Jinlong bauxite sourced from Guangxi Province, China

Abstract: Characteristic samples from the No. 1 ore body of the Jinlong bauxite deposit in Guangxi Province, China, were assessed to determine their chemical composition using whole-rock geochemical analysis, their mineral components using X-ray diffraction, their thermal characteristics via differential thermal analysis, thermogravimetry and differential thermogravimetry, and their dissemination characteristics by scanning electron microscopy/energydispersive spectrometry. The results show that the average Al 2 O 3 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This reaction (i.e., 2FeOOH → Fe 2 O 3 + H 2 O) occurs at temperatures between 300 and 344 • C [35] or 270 and 330 • C [36], and it is commonly associated with a mass loss of 10% or less if there are secondary phases. This mass loss coincides with an endothermic peak around 325 • C in the DTA curve (Figure 5b) that is considered as the result of the breakdown of goethite [34][35][36].…”
Section: Mineralogy and Petrographysupporting
confidence: 56%
See 1 more Smart Citation
“…This reaction (i.e., 2FeOOH → Fe 2 O 3 + H 2 O) occurs at temperatures between 300 and 344 • C [35] or 270 and 330 • C [36], and it is commonly associated with a mass loss of 10% or less if there are secondary phases. This mass loss coincides with an endothermic peak around 325 • C in the DTA curve (Figure 5b) that is considered as the result of the breakdown of goethite [34][35][36].…”
Section: Mineralogy and Petrographysupporting
confidence: 56%
“…In Loma Caribe deposits, and according to XRPD (samples LC-6, LC-7 and LC-7_black), lithiophorite is ubiquitous with clear peaks at 9. Thermogravimetry showed that samples from Loma Caribe experience a mass loss of about 4% before 260-280 °C, probably due to the loss of adsorbed water for temperatures below 110-160 °C [33,34] and to the transformation of gibbsite to boehmite, which is reported to occur at temperatures between 150 and 260 °C [34] (Figure 5a). Between 260 and 320 °C, the mass loss is between 5 and 8%.…”
Section: Mineralogy and Petrographymentioning
confidence: 99%
“…Although the overall course of the processes is widely known, the effects of various crystal-chemical and chemical factors on the transformation mechanisms and properties of the products are still under vigorous debate [1,3]. This type of research focuses usually on monomineral synthetic samples [e.g., [4][5][6][7][8][9][10] and does not fully reflect the complexity of the processes during thermal transformations of natural Fe-oxide-rich materials [e.g., [10][11][12][13][14][15][16][17], archeological findings [18,19] and composite industrial products or wastes [20][21][22]. A good example of such a complex system are bog iron ores.…”
Section: Introductionmentioning
confidence: 99%
“…Since the BDS was put into use, many scholars in China and abroad have done plenty of researches on its performance of BDS alone, or GPS + BDS combined [5][6][7][8]. Zhang et al [9] show that the accuracy of a static baseline (medium baseline, <100km) using the four-hour long BDS measurement data based on the broadcast ephemeris reached 4cm. Pu et al and Wu et al [10,11] analyzed the relative positioning performance using the combination of the GPS, BDS and Galileo systems with the short baseline hybrid double-difference and short baseline single epoch tight combination.…”
mentioning
confidence: 99%